Philippine multilingual medical thesaurus on diseases - pathological conditions, signs, and symptoms in Waray - Balanquit, Loiue Stihl L.
This study was conducted to translate MeSH terms on Diseases: Pathological conditions, signs and symptoms into Waray to become part of the Philippine Multilingual Medical Thesaurus.